Screening for hypertension using emergency department blood pressure measurements can identify patients with undiagnosed hypertension: A systematic review with meta‐analysis. Issue 9 (6th August 2019) - Armitage, Laura C.; Whelan, Maxine E.; Watkinson, Peter J.; Farmer, Andrew J.
Abstract: Hypertension is the leading risk factor for death globally. A significant percentage of patients admitted to hospital have undiagnosed hypertension, yet recognition of elevated blood pressure (BP) in hospital and referral for post‐discharge assessment are poor. Physician perception that elevated inhospital BP is attributable to anxiety, pain, or white coat syndrome may underlie an expectation that BP will normalize following discharge. However, these patients frequently remain hypertensive. The authors conducted a systematic review to evaluate the extent to which elevated inhospital BP can predict the presence of hypertension in previously undiagnosed adults. The authors included cohort studies in which hospital patients whose BP exceeded the study threshold underwent further post‐discharge BP assessment following discharge. Twelve studies were identified as eligible for inclusion; a total of 2627 participants met review eligibility criteria, and follow‐up BP data were available for 1240 (47.2%). Median percentage of patients remaining hypertensive following discharge was 43.6% (range: 14.2‐76.5). Across 7 studies which identified people with possible hypertension using an index test threshold of 140/90, the pooled proportion subsequently identified with hypertension at follow‐up was 43.4% (95% CI: 25.1%‐61.8%). This review indicates that screening for hypertension in the emergency hospital environment consistently identifies groups of patients with undiagnosed hypertension. Unscheduled hospital attendance therefore offers an important public health opportunity to identify patients with undiagnosed hypertension.